Sufism and social media: Correlation between WhatsApp usage and the level of religiosity of PP Jagad Alif students - Santang, Ahmad Kian; Setiawan, Benni (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the correlation between WhatsApp usage and the religiosity level of PP Jagad Alif santri, as well as the factors influencing this correlation. A correlational quantitative approach was used to measure the relationship between these two variables. A sample of 58 individuals was selected using simple random sampling from a population of 68 santri at PP Jagad Alif, calculated with the Slovin formula. Data were collected through surveys using the SMUI instrument for WhatsApp and the CRS instrument for religiosity, with each instrument demonstrating a validity of 0.9 Pearson's r and reliability scores of 0.996 and 0.995 Cronbach's Î±, respectively. Data analysis techniques included Pearson correlation and simple linear regression to test the hypothesis. The results showed a positive correlation of 0.349 with a p-value of 0.004, and the contribution of the social media variable to religiosity was 12.2%. These findings indicate that the correlation between social media usage and the religiosity level of PP Jagad Alif santri is weak.